(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the state of lending banks on the further development of the banking sector in our country, and also the quality of the loan portfolio. Analyzes the state change of the credit policy is currently based on control of the quality of the loan portfolio of second tier banks of Kazakhstan. In the analysis of the data of the National Bank of Kazakhstan on quality control of credit portfolio. And also indicates the current quality of the loan portfolio of the Republic of Kazakhstan and the main priorities of the changes in credit policy in the dynamics of lending in the banking sector. Proposed solutions to problems and ways of improvement of credit policy and loan quality. One of the elements of effective management: credit policy and its development, i.e. the quality of the loan portfolio is of particular importance. In this connection there is a need to determine the quality of loan portfolios of second tier banks of Kazakhstan.